Clínica lacaniana da anorexia - Evaristo Nunes de Magalh?es (2014)
This paper aims to discuss the Lacanian clinic of anorexia. Therefore, a qualitative methodology that included a literature review and a field survey was used. We consulted the main authors who study anorexia and refer to the Lacanian theory. Nine professionals working in this area were interviewed. Throughout the work, we sought to interconnect field/literature. The work was divided into four chapters. The first one discusses the arrival of the anorexic patient to the clinic. In general, Anorexic girls do not seek psychoanalysts by themselves. Most of the times, they are led to the clinic by their parents, more specifically, by their mothers. There is no clear demand. Demand usually comes from a person seeking knowledge about himself. Such fact does not occur in anorexia since food refusal is not seen as a problem. What don´t these girls demand? What do they not want to know? What, in fact, are they refusing? Eating nothing in anorexia means anesthetizing the suffocating mother who suffocates through porridge the structural distortion of body image, sex and femininity in all its implications. Second and third chapters discusses the interruption of this demand circle, almost inexistent for these people. The deadly anorexic circle only finds limit when life is at risk. At this time also, it is not possible to talk of demand in the psychoanalytic sense. There is, rather, a call for help. The psychoanalyst can not neglect such request. It is necessary, through transfer, to twist this call in order to imply the patient in her symptom. This subjective rectification is only possible because it is grounded in the following clinical assumptions: the construction of the clinical case, the interpretation of the refusal, the desire of the analyst and the analytic act. Having said that, we studied two experiences of psychoanalytic treatment in severe cases in Italy. The fourth chapter discusses anorexia contemporary Lacanian clinic. We propose a different view of the anorexia understanding and treatment. The view is not about the interpretation of the symptom any longer. Anorexia is seen as a possible link to be built from the real body image. This is where the symptom does not dive into the interpretation. There is a permanence of the symptom. The analyst's role is to bear all that in order to prevent it from overflowing and endangering individuals lives. The interviews transcripts were enclosed in the annexes.